Tourism Attractions and Infrastructures Evaluation in Loksado Tourism Area, Hulu Sungai Selatan Regency, South Kalimantan - Arifin, Yulian Firmana (Graduate School, Universitas Brawijaya, 2017)
The aim of the study is to evaluate descriptively the tourism attraction and infrastructure in Loksado, Hulu Sungai Selatan Regency, South Kalimantan. Field data was collected through ground checking and listing all aspects of infrastructures, including the condition of road, transportation, accommodation, bridge, houses, and conditions of tourism object. The result shows that tourism grows significantly in Hulu Sungai Selatan Regency, with Loksado area as a hot spot for tourism activities and developments. Loksado is productive in term of natural and cultural resources that are potential to develop as the tourist attraction. However, there are problems related to the accessibility with main threat from slippery clay path and landslide. Many build facilities and infrastructures seem to be less managed, and many of them are in development phases. These lead to the weaknesses of the tourism development in Loksado. Community-based tourism appears to be important to promote, with the particular objectives is increasing the local benefit to increase community participation in tourism attraction and infrastructure management. It is also possible to increase local community in accommodation services. Keywords: infrastructure, landslide, Loksado, tourism facility, tropical forest